FLUORESCENT NANOPARTICLES LOADED WITH RHENIUM COMPOUNDS AND THEIR BIOCOMPATIBILITY WITH ERYTHROCYTES - A. V. Slipkan; M. I. Kharlova; A. V. Shtemenko; N. I. Shtemenko (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2019)
The use of nanotechnology in modern medicine is a contemporary area of research. Both rhenium(III) cluster compounds and rhenium(I) tricarbonyls have a whole spectrum of biological activity. Red blood cells are a convenient model for studying of the biocompatibility and toxicity of nanocomposites. Thus, the purpose of the work was synthesis of fluorescent nanoparticles based on zirconium phosphate (ZrP), which contain dichlorotetra-μ-isobutirate dirhenium(III) (I), and phosphatidylcholine-based nanoliposomes containing fluorescent bromotricarbonyl-5(1,2,3trimethoxybenzene)-3 (pyridin-2-yl)-1,2,4-triazolrhenium(I) (II) and to find out their biocompatibility and toxicity humans and mouse erythrocytes. Fluorescent ZrP-based nanoparticles containing I were synthesized by modifying the surface of nanoparticles with rhodamine-B (ZrP-I-RB). Liposomes containing II were synthesized with phosphatidylcholine using the thin film hydration method (IIlip). Both types of nanoparticles had fluorescent properties. Fluorescent images of human and mouse erythrocytes in experiment with incubation with ZrP-I-RB and IIlip in final concentrations of nanoparticles 1×10-6M, 1×10-7M and 1×10-8M showed that the synthesized nanoparticles were biocompatible with erythrocytes and after 1-5-30 -90 minutes effectively was absorbed by the cells. The absorption efficiency, which was measured by the dependence of the fluorescent intensity from the time of incubation of cells with nanoparticles of the certain final concentration, depended on the  biochemical composition of the erythrocyte membrane, which differs in human and mouse erythrocytes and in healthy mice and mice with a spontaneous tumor. The obtained results shows importance of the further studies of fluorescent nanoparticles loaded with rhenium compounds with the aim to introduct them into medical practice as dual-purpose medicines for treatment and visualization of pathological cells.